Cartap removal through Fenton oxidation in a fluidized-bed reactor - Rabongue, Anamie; De Luna, Mark Daniel G.; Lu, Ming-Chun (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
The presence of organic pollutants specifically pesticides in the aqueous environment is an emerging problem that requires immediate attention. In this study, the applicability of fluidized-bed Fenton process in the removal of commonly used pesticides such as cartap was investigated. The effects of initial cartap concentration, initial hydrogen peroxide concentration, initial ferrous ion concentration and solution pH on cartap removal were evaluated. Also, the reaction rate was fitted in pseudo-first order and pseudo-second order kinetics and a mathematical model was employed in the study. Initial hydrogen peroxide concentration, initial ferrous ion concentration and solution pH were optimized using Box-Behnken design and artificial neural network (ANN) to achieve maximum cartap removal. Results showed that fluidized-bed Fenton process successfully removed at least 95% cartap within 2 h. Validation experiments for both BBD and ANN resulted in standard error of less than 4.5% and it was found that hydrogen peroxide was the most important factor in the process. Moreover, fluidized-bed Fenton process was applied to cartap solutions containing inorganic salts such as nitrate (NO3-), phosphate (PO43-) and sulfate (SO42-) to simulate near actual environmental conditions.
Thesis (Master of Science in Environmental Engineering)--University of the Philippines Diliman
Keywords: Water -- Purification -- Oxidation; Micropollutants